2021
DOI: 10.1038/s41598-021-01381-5
|View full text |Cite
|
Sign up to set email alerts
|

Application of digital infrared thermography for carpal tunnel syndrome evaluation

Abstract: We investigated the thermographic findings of carpal tunnel syndrome (CTS). We enrolled 304 hands with electrodiagnostically identified CTS and 88 control hands. CTS hands were assigned to duration groups (D1, < 3 months; D2, 3‒6 months; D3, 6‒12 months; D4, ≥ 12 months) and severity groups (S1, very mild; S2, mild; S3, moderate; S4, severe). The temperature difference between the median and ulnar nerve territories (ΔM-U territories) decreased as CTS duration and severity increased. Significant differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 50 publications
2
17
0
Order By: Relevance
“…Damage to unmyelinated small bers in the early stages of CTS may increase thermal variation in areas innervated by the same nerve through mechanisms such as sympathetic dysfunction, reactive vasoconstriction, and antidromic sensory ber activation [23]. We have reported in a previous study that as the severity of CTS increases, the anisometry also gradually increases [19]. In this study, infrared thermographic changes were observed, along with pain reduction and clinical improvement after CTR.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Damage to unmyelinated small bers in the early stages of CTS may increase thermal variation in areas innervated by the same nerve through mechanisms such as sympathetic dysfunction, reactive vasoconstriction, and antidromic sensory ber activation [23]. We have reported in a previous study that as the severity of CTS increases, the anisometry also gradually increases [19]. In this study, infrared thermographic changes were observed, along with pain reduction and clinical improvement after CTR.…”
Section: Discussionsupporting
confidence: 52%
“…Speci cally, secondary parameters, such as ΔM − U digits, Δthenar − hypothenar, and ΔM − U territories did not show signi cant changes after surgery. According to our previous study, these parameters, as opposed to anisometery, stand out in the early stage of the disease, but become less apparent as the severity and duration of the disease increases [19]. Those who underwent surgery were electrodiagnostically severe in most cases (88.9%), with an average prolonged symptom duration of 12.0 months.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Therefore, early detection is important for effective treatment, and various techniques based on infrared thermography will aid in diagnosis; computer-aided diagnosis can also be useful [ 28 ]. Park et al, reported that in carpal tunnel syndrome (CTS), DITI uses a different approach depending on the disease duration and severity and may play a complementary role in understanding and evaluating CTS [ 29 ]. DITI is also used in sports medicine.…”
Section: Discussionmentioning
confidence: 99%